Assessing the impacts of climate change on drought-prone regions in Bhima sub-basin (India) using the Standard Precipitation Index. Issue 2 (24th September 2021) - Laddimath, Rajashekhar S.; Patil, Nagraj S.; Rao, P. S.; Nagendra
Abstract: In Bhima sub-basin, the water sector is at high demand and in critical stress due to rapid urbanization. The past few decades have witnessed extreme events and seasonal shifts due to anthropogenic activity triggered climate change. Thus, to evaluate the variability of extreme events, assessing the historical and future trends of precipitation in climate change scenarios is vital for developing comprehensive mitigation and adaptation strategies. This paper examines the drought-prone regions by studying spatio-temporal variation of drought scenarios using the Standard Precipitation Index (SPI). The change factor method is used to downscale precipitation data from general circulation model (GCM) outputs under four Representative Concentration Pathway (RCP) scenarios to project future downscaled precipitation, to be input to examine the drought for 12 months. GCM and scenario uncertainty in climate change impact assessments are examined using box-whisker plots. Temporal variation for 12-month SPI shows significant changes over RCP scenarios. For the beginning of the period, 2021 precipitation is scanty for RCP 2.6 and 4.5 scenarios. Mild to moderate and severe drought events for the RCP 2.6 scenario are more predominant. Severe drought events under the RCP 6.0 scenario dominate over others. Lastly, the inconsistent pattern of drought events for RCP 8.5 is reported. HIGHLIGHTS: Impacts of climate change on drought : regional scenario in Bhima sub-basin. Trend analysis using Mann-Kendall test to examine the baseline climate. Analysis of drought characteristics by Standardized Precipitation Index (SPI). Occurrence of drought events under CMIP5 model/RCP scenarios in different grids of the study area. Temporal variation and spatial pattern of the drought characteristics for 12-month SPI.